PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI SARANA PROMOSI UKM DI KABUPATEN JEPARA - Azizah - Azizah (Politeknik Negeri Semarang, 2014)
The number of SME (Small Medium Enterprises) locating in Jepara with a lot of product variance make this district become more popular. SME locations’ mapping is made in purpose promoting these SMEs. There are 2 categories’ sample in this observation, they are regional sample and SMEs sample. This mapping result will be published in the webblog in order to make the existance of the Jepara’s SMEs are known by the public.